Never get angry again : the foolproof way to stay calm and in control in any conversation or situation - Lieberman, David J. (St. Martin's Press, 2018)
A holistic look at the underlying emotional, physical, and spiritual causes of anger cites the shortcomings of traditional anger-management techniques while explaining how to shift one's perspective to maintain a state of calm.